The Influence of Profitability, Leverage, Company Size, and Fixed Asset Intensity on Tax Avoidance in the Consumer Goods Industry - Rois, Dimas Ilham Nur; Astungkara, Agni; Kurniati, Sari; Hasanah, Aini Nur (Journal of Management and Administration Provision, 2024)
This research aims to analyze the influence of profitability, leverage, and asset intensity on tax avoidance. This research includes quantitative research using secondary data obtained from company annual reports. The population of this research is companies in the consumer goods and industrial sector listed on the Indonesia Stock Exchange (BEI) in 2020-2022. A total of 103 samples were selected using the purposive sampling method and analyzed using multiple linear regression. The research results show that profitability, leverage, and company size affect tax avoidance, while fixed asset intensity does not affect tax avoidance. The limitations of this research are still limited to the goods industry and consumption sectors.